Oxidative Stress Plays an Important Role in Glutamatergic Excitotoxicity-Induced Cochlear Synaptopathy: Implication for Therapeutic Molecules Screening - Anissa Rym Saidia; Florence François; François Casas; Ilana Mechaly; Stéphanie Venteo; Joseph T. Veechi; Jérôme Ruel; Jean-Luc Puel; Jing Wang (Antioxidants, 2024)
The disruption of the synaptic connection between the sensory inner hair cells (IHCs) and the auditory nerve fiber terminals of the type I spiral ganglion neurons (SGN) has been observed early in several auditory pathologies (e.g., noise-induced or ototoxic drug-induced or age-related hearing loss). It has been suggested that glutamate excitotoxicity may be an inciting element in the degenerative cascade observed in these pathological cochlear conditions. Moreover, oxidative damage induced by free hydroxyl radicals and nitric oxide may dramatically enhance cochlear damage induced by glutamate excitotoxicity. To investigate the underlying molecular mechanisms involved in cochlear excitotoxicity, we examined the molecular basis responsible for kainic acid (KA, a full agonist of AMPA/KA-preferring glutamate receptors)-induced IHC synapse loss and degeneration of the terminals of the type I spiral ganglion afferent neurons using a cochlear explant culture from P3 mouse pups. Our results demonstrated that disruption of the synaptic connection between IHCs and SGNs induced increased levels of oxidative stress, as well as altered both mitochondrial function and neurotrophin signaling pathways. Additionally, the application of exogenous antioxidants and neurotrophins (NT3, BDNF, and small molecule TrkB agonists) clearly increases synaptogenesis. These results suggest that understanding the molecular pathways involved in cochlear excitotoxicity is of crucial importance for the future clinical trials of drug interventions for auditory synaptopathies.